Penyisihan COD, BOD Dan TSS Pada Limbah Cair Tahu Secara Koagulasi-Flokulasi Dengan Variasi Dosis Biokoagulan Lidah Buaya Dan Kecepatan Pengadukan - Safira Ulyani; Syarfi Daud; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Tofu liquid waste contains organic compounds which are generally high. One of the treatments to reduce pollutant level in tofu liquid waste is coagulation and flocculation. The aim of this study was to study the effect of variations dosage of Aloe vera and the speed of stirring on the removal of tofu liquid waste by coagulation and flocculation using the Aloe vera as biocoagulant. This research was carried out with variations dosage of Aloe vera of 80; 120 dan 160 ml/l and the stirring speed variations of 30; 60 dan 90 rpm. The results showed the highest removal efficiency of COD, BOD and TSS at a dose of coagulant 160 ml/ l with a stirring speed of 60 rpm each of 61,90%, 49,97% and 89,73% Keywords: Tofu Liquid Waste, Dosage, Stirring Speed, Coagulation-Flocculation, Aloe Vera.